Household tales by the brothers grimm ebook - Grimm, Jacob (Duke Classics, 2012)
The primal beating heart at the center of much of the Western literary canon can be found in the folk stories, myths, and fairy tales collected by the amateur folklorists Wilhelm and Jacob Grimm. Surprisingly graphic in comparison to their sanitized twentieth-century retellings, these intense tales are not for the faint at heart. A must-read for any fan of folklore.